PENGARUH RETURN ON ASSET DAN NET PROFIT MARGIN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAA SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2020 - Muhammad Rivandi; Feby Oktaviani (Jurnal Inovasi Penelitian, 2022)
Profit growth is the difference between the profit generated from a period with the profit generated in the previous period. The purpose of this study is to obtain empirical evidence regarding the effect of Return On Assets (ROA) and Net Profit Margin (NPM) on Profit Growth. The population of this study are cement companies listed on the IDX. The sample in this study were 7 companies selected by purposive sampling method. The analytical method used is the panel data regression method. Based on the hypothesis, the research results indicate that Return on Assets has no effect on profit growth and Net Profit Margin has a positive effect on Profit Growth